Uji Tanam Pot Biodegradable Berbahan Limbah Biomassa Pelepah Pisang Kepok (Musa paradisiaca L.) dan Jerami Padi (Oryza sativa L.) untuk Tanaman Cabai Rawit (Capsicum frutescens L.) pada Fase Vegetatif - Agustin, Churia Camelia; Rahmawati, Winda; Amien, Elhamida Rezkia; Suharyatun, Siti (abe.fp.unila.ac.id, 2025)
Biodegradable pots made from biomass waste offer an environmentally friendly alternative to replace plastic polybags in plant cultivation. This study aimed to evaluate the effect of different raw materials used in making biodegradable pots on the vegetative growth of chili pepper plants. Two treatments were applied: pots made from Kepok banana stem fibers (B1) and pots made from rice straw (B2), each with four replications. The observed parameters included root length, plant height, stem diameter, and number of leaves over 27 days after planting. The results showed that pots made from rice straw produced better growth in all parameters compared to those made from banana stem fibers. The longest root length was found in treatment B2U1 (19 cm), the tallest plants in B2U2 (23.6 cm), and the largest stem diameter also in B2U2 (0.37 cm). These differences are attributed to the physical characteristics of the raw materials: rice straw pots have lower density and a porous structure that facilitates root penetration and growth, while banana stem pots have higher density and fiber mass, resulting in a denser structure that restricts root development. Therefore, it can be concluded that biodegradable pots made from rice straw are more effective in supporting the vegetative growth of chili pepper plants than those made from banana stem fibers. Keywords: Banana Stem, Biodegradable Pot, Densities, Kepok Banana Stem, Rice Straw, Vegetative Phase.